Effect of Kaolin and Phonolite Particulates Addition on Hardness and Abrasive Wear Behavior of Glass−Fiber Composites (The International Journal of Engineering & Information Technology (IJEIT), 2025)
The aim of this experimental investigation is to study the hardness properties and abrasive wear behavior of glass fiber reinforced polymer (GFRP) composites modified with kaolin and phonolite particles as natural fillers. Three composites were fabricated by hand lay-up method using chopped glass fibers as reinforcement agent and unsaturated polyester resin as a matrix material. The first composite was prepared without any particulate additions to serve as a reference; the other two composites were prepared by incorporating the kaolin and phonolite particles at weight percentage of 10% in the polyester resin, respectively. Brinell hardness test was conducted to determine the hardness values of the composites, and the abrasive wear performance was evaluated using two-body abrasive wear test. Experimental results revealed that the addition of kaolin and phonolite particles improved both the wear resistance and hardness of the studied composites; nevertheless, the significant improvements were observed with phonolite-filled composite, the hardness and wear resistance of this composite were increased by 69% and 24.3%, respectively. The findings of this study indicate that the lack of abrasive wear resistance and hardness properties of GFRP composite which limit their use as wear-resistant materials can be improved or overcome by selecting and using of proper particulate fillers.